Christians under the crescent and Muslims under the cross c.630-1923 - Berto, Luigi Andrea (Routledge, Taylor & Francis Group, 2021)
Prohibitions, laws and justice -- Conversions -- Working -- Sharing beliefs and spaces -- Attacking the other -- Eliminating the other.